2014
DOI: 10.4103/2277-9175.133201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CD52 positive sperms in subfertile human semen samples: Is there any relationship with main semen parameters?

Abstract: Background:Sperm maturation and sperm membrane integration are the most important elements in male fertility. CD52 is one of the antigens. CD52 is a GPI (glycosylphosphatidylinositol) anchored that express on lymphocytes and epididymal cells. This antigen bind to sperm membrane during transition sperm from epididymal duct as well as its relationship with semenogelins in human seminal plasma. The aim of this study was to obtain any association between the percentage of CD52 positive sperms with main semen param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Flow cytometry results showed that the presence of PRR has a negative effect on sperm quality. Other membrane surface proteins are also negatively involved in sperm motility such as membrane antigen CD52 [ 37 ], neprilysin (NEP) [ 38 ], μ-opioid receptor (MOR) [ 39 ] or testicular isoform of angiotensin converting enzyme (tACE) [ 13 ]. Taking into account that sperm motility appears to be essential for natural reproduction, currently, the motility assay is the most reliable predictor of male factor infertility [ 12 , 37 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry results showed that the presence of PRR has a negative effect on sperm quality. Other membrane surface proteins are also negatively involved in sperm motility such as membrane antigen CD52 [ 37 ], neprilysin (NEP) [ 38 ], μ-opioid receptor (MOR) [ 39 ] or testicular isoform of angiotensin converting enzyme (tACE) [ 13 ]. Taking into account that sperm motility appears to be essential for natural reproduction, currently, the motility assay is the most reliable predictor of male factor infertility [ 12 , 37 , 40 ].…”
Section: Discussionmentioning
confidence: 99%